ANALISIS PERTUMBUHAN EKONOMI DITINJAU DARI INVESTASI DAN TENAGA KERJA DI INDONESIA TAHUN 2015-2020 - Erickson Sinaga; Fredysyah Putra; Jogi Situmorang; Excaudia Siringo-ringo (STKIP Subang, 2026)
Economic growth is one of the main indicators used to assess the success of economic development. However, Indonesia's economy experienced a contraction in 2020 due to the COVID-19 pandemic, which affected investment activities and labor absorption. This study aimed to analyze the effect of investment and labor on Indonesia's economic growth during the period 2015–2020, both partially and simultaneously. This study employed a quantitative approach with a descriptive correlational design using annual time series secondary data obtained from the Central Bureau of Statistics (BPS) and the Ministry of Investment/Investment Coordinating Board (BKPM). Data were analyzed using multiple linear regression with the assistance of Statistical Package for the Social Sciences (SPSS), preceded by classical assumption tests. The results showed that investment had a positive coefficient, while labor had a negative coefficient on economic growth. However, partially, investment and labor did not have a significant effect on economic growth. Simultaneously, both variables also did not significantly affect Indonesia's economic growth during the study period. These findings indicate that economic growth is influenced by various factors beyond investment and labor.